The Practice of Multicultural Education at Majelis Taklim in Sitiung Dharmasraya, West Sumatra - Darul Ilmi; Melia Afdayeni; Kori Lilie Muslim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to describe the existence of the majelis taklim (Islamic forum) and how this majelis taklim strengthen its role in providing multicultural education for multicultural communities in Sitiung Dharmasraya, West Sumatra. In contrast to several studies which show that the majelis taklim is an agent of spreading intolerant narratives in society, this article tries to present the face of the majelis taklim that is friendly to diversity by strengthening multicultural education. This study uses a participatory action research method. Data were obtained through interviews, focus group discussion, observations, documentation, and actions or improvements through workshops in the July-November 2018 period at majelis taklim in Sitiung Dharmasraya, West Sumatra. The findings of this study indicate that the majelis taklim in Sitiung are attended by people who come from various elements and backgrounds and different mindsets, but the attitude of togetherness is maintained and synergized. In addition, the existing majelis taklim are used as a forum for increasing awareness of community members who are starting to feel the impact of modernization and globalization, and are starting to plunder solidarity and tolerance. The strengthening of multicultural education carried out through participatory action research in this study shows that the taklim assembly can function as a center for peace values, a center for change agents to become better Muslims, a community development center, communication and information center, a cadre center and a social control agent. Artikel ini bertujuan untuk mendeskripsikan eksistensi majelis taklim dan memperkuat perannya dalam menghadirkan pendidikan multikultural bagi masyarakat multikultural di Sitiung Dharmasraya, Sumatera Barat. Berbeda dengan beberapa studi yang menunjukkan bahwa majelis taklim menjadi agen penyebar narasi intoleran di masyarakat, artikel ini berusaha menghadirkan wajah majelis taklim yang ramah keragaman dengan usaha memperkuat pendidikan multikultural. Studi ini menggunakan metode participatory action research. Data diperoleh melalui wawancara, focus group discussion, observasi, dokumentasi, serta aksi atau penguatan melalui workshop pada periode Juli-November tahun 2018 di majelis taklim yang ada di Sitiung Dharmasraya, Sumatera Barat. Temuan studi ini menunjukkan bahwa majelis taklim-majelis taklim yang ada di Kecamatan Sitiung diikuti oleh masyarakat yang datang dari berbagai unsur dan latar belakang serta pola pikir yang berbeda, namun sikap kebersamaan tetap terjaga dan bersinergi. Selain itu, kelompok majelis taklim yang ada dijadikan sebagai wadah untuk peningkatan kesadaran anggota masyarakat yang mulai merasakan dampak modernisasi dan globalisasi, serta mulai menjarah solidaritas dan toleransi. Penguatan pendidikan multikultural yang yang dilakukan melalui participatory action research dalam studi ini, menunjukkan bahwa majelis taklim dapat berfungsi sebagai pusat nilai perdamaian, pusat agen perubahan untuk menjadi umat Islam yang lebih baik, pusat pengembangan masyarakat, pusat komunikasi dan informasi, pusat kader dan agen kontrol sosial.